2021
DOI: 10.1039/d0fd00121j
|View full text |Cite
|
Sign up to set email alerts
|

Molecular fragmentation as a way to reveal early electron dynamics induced by attosecond pulses

Abstract: We present a theoretical study of the electron and nuclear dynamics that would arise in an attosecond two-color XUV-pump/XUV-probe experiment in glycine. In this scheme, the broadband pump pulse suddenly...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 73 publications
1
18
0
Order By: Relevance
“…There is theoretical evidence that nuclear degrees of freedom in a large molecule weaken coherence. Still, it is remarkable that even in the worst-case scenario phase relations may survive [216]. The present review is a brief illustration of how phase space tools widely used in other research areas, such as quasiprobability densities, may be employed in attosecond physics.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…There is theoretical evidence that nuclear degrees of freedom in a large molecule weaken coherence. Still, it is remarkable that even in the worst-case scenario phase relations may survive [216]. The present review is a brief illustration of how phase space tools widely used in other research areas, such as quasiprobability densities, may be employed in attosecond physics.…”
Section: Discussionmentioning
confidence: 99%
“…Thereby, a key question is how to adapt these techniques to a highly transient, subfemtosecond regime, in the context of attochemistry. Recently, quantum and classical approaches have been combined to investigate electron and nuclear dynamics in pump-probe experiments in glycine, and the initial state was computed using phase space techniques [216]. Even in the single-electron regime, it is desirable to move from one-dimensional models.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies using pump-probe schemes in H 2 have shown that coupling of electronic and vibrational degrees of freedom affects coherence and may hinder electron localisation [97]. Still, studies in large molecules indicate that phase relations may be preserved even in systems with many degrees of freedom [98], and could even be controlled leading to tailored ionisation enhancement or suppression [99]. Our simplified model is meant as a proof of concept and a first step towards more realistic scenarios.…”
Section: Discussionmentioning
confidence: 99%